"Accessories included": Armed Christians and the mythos of heroic violence. (August 2020) - Utter, Benjamin D.
The myth of the "good guy with a gun" is a seductive one for Americans, who cite self-defense as the foremost reason for gun ownership, and Pew data show that white, self-identified evangelicals are more likely than members of other faith groups or the average citizen to own and carry a gun. This fantasy of the individual hero's efficacy is enticing but, I argue, incoherent. Through comparison of past and present Southern Baptist Convention resolutions on gun violence and a close reading of gun rights advocacy rhetoric, I show how biblical language and heroic biblical exemplars are exploited to fuse fantasies of highly individualistic, personal power with a glorification of national power. The iconography of gun manufacturer merchandise perpetrates a misreading of history and Scripture, and, at least implicitly, of medieval romantic texts, as well. Careful attention to gun manufacturer advertising iconography, and to the medieval textual tradition that it appropriates, reveals a warning that the self-authorized hero, lethally "accessorized, " is as likely to threaten the safety of the community he serves as to guard it.